2011
DOI: 10.1371/journal.pone.0014576
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Virally Vectored Autoimmunity as a Biocontrol Strategy for Cane Toads

Abstract: BackgroundThe cane toad, Bufo (Chaunus) marinus, is one of the most notorious vertebrate pests introduced into Australia over the last 200 years and, so far, efforts to identify a naturally occurring B. marinus-specific pathogen for use as a biological control agent have been unsuccessful. We explored an alternative approach that entailed genetically modifying a pathogen with broad host specificity so that it no longer caused disease, but carried a gene to disrupt the cane toad life cycle in a species specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The fully aquatic life cycle of X. laevis may result in unique immunological adaptations that are not shared with amphibian species that live terrestrially after metamorphosis. Pallister et al [50] suggested that differences in larval development might contribute to differences in immune function. Indeed, comparative immunological studies between X. laevis and other anuran species are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The fully aquatic life cycle of X. laevis may result in unique immunological adaptations that are not shared with amphibian species that live terrestrially after metamorphosis. Pallister et al [50] suggested that differences in larval development might contribute to differences in immune function. Indeed, comparative immunological studies between X. laevis and other anuran species are needed.…”
Section: Discussionmentioning
confidence: 99%
“…So far, efforts to identify a truly cane toad‐specific pathogen for use as a biological control agent have been unsuccessful, as have been efforts to induce autoimmunity and disrupt metamorphosis (Pallister et al ., ). Alarm pheromones and translocation of parasitic lungworms to the invasion front may provide new tools in the management of this damaging pest species (Saunders et al ., ).…”
mentioning
confidence: 97%
“…Such strategies were explored for the management of vertebrate pests, such as rodents, rabbits, cane toads, and carp, in Australia [53]. However, major challenges regarding efficacy (i.e., insufficient duration of sterility) and delivery (i.e., ineffective transmission of the viral vector) were reported for such applications [54][55][56][57]. Most of these approaches have been abandoned in the meantime, and only the use of pathogenic non-GM viruses to control invasive fish species, such as tilapia or carp, is still being evaluated [58,59].…”
mentioning
confidence: 99%